ANALISIS PENGENDALIAN KUALITAS PRODUK BATAKO PADA PT BODEM MAS JAYA - Ardianto, Pujo; Prasetyo, Bahariandi Aji (LPPM Universitas Putera Batam, 2025)
PT Bodem Mas Jaya is a company engaged in the production and distribution of concrete blocks in Batam City. From December 2023 to November 2024, the company faced quality control issues, with the defect rate consistently exceeding the maximum allowable limit of 3%. This affected the company’s ability to meet market demand optimally. This study aims to analyze quality control in the concrete block production process and evaluate the results of implemented improvement initiatives. The method used is Six Sigma with the DMAIC (Define, Measure, Analyze, Improve, Control) approach. The analysis showed that before improvements, the production process had an average DPMO of 20,510.7 with a sigma level of 3.54, and the number of defective products reached 14,395 pcs out of a total output of 132,517 pcs. After implementing improvements such as morning briefings, SOP development, sand filtering, machine maintenance, and cleaning of the production area, process performance improved. The average DPMO decreased to 17,004.8, the sigma level increased to 3.62, and the percentage of good products rose to 95% – 99%, with the number of defective products reduced to 6,200 pcs out of a total output of 121,622 pcs during the period from December 2024 to May 2025.